Recycling of an agricultural bio-waste as a novel cellulose aerogel: a green chemistry study - KAYA, MİTHAT (My University, 2020)
Cellulose aerogel (CA) isolated from tea stem wastes (TSW) is a good fire retardant and heat insulator, environmentally friendly, thermally stable and highly porous material with a network structure. These outstanding properties have attracted a huge interest in the materials world. In this study, firstly, following delignification and removing hemicellulose, pure raw cellulose was isolated using TSW, hydrogel form of cellulose was prepared by regeneration of cellulose solution, and then, the final product (CA) was produced via freeze-drying. The data results showed that the aerogel had a three dimensionally network structure. Moreover, it can be deduced that thermal durability of the studied CA could be effective because of its fire retardant and heat insulating property. In addition, the production process of CA is easily available at low cost and sustainable.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; MÜHENDİSLİK, ÇEVRE; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); POLİMER BİLİMİ; Temel Bilimler (SCI); ENGINEERING, ENVIRONMENTAL; ENGINEERING; Engineering, Computing & Technology (ENG); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Polimerler ve Plastikler; Atık Yönetimi ve Bertarafı; Kirlilik; Çevre Mühendisliği; Çevre Kimyası; Genel Mühendislik; Mühendislik (çeşitli); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Polymers and Plastics; Waste Management and Disposal; Pollution; Environmental Engineering; Environmental Chemistry; General Engineering; Engineering (miscellaneous); Chemistry (miscellaneous); General Chemistry; Physical Sciences; Cellulose; Bio-polymer; Hydrogel; Aerogel; Tea stem; THERMAL-CONDUCTIVITY; NANOPARTICLES; PERFORMANCE; FABRICATION; Cellulose; Bio-polymer; Hydrogel; Aerogel; Tea stem